Utilization of Hypertension Management Guidelines in Primary Healthcare Facilities in Tharaka Nithi County, Kenya - KAMETI, ELIJAH; Mugambi, Joy; Opare-Addo, Paul (JOURNAL OF CLINICAL CARE AND MEDICAL ADVANCEMENT, 2024)
Hypertension (HTN) is a leading contributor to the global burden of non-communicable diseases (NCDs). The effective management of hypertension constitutes an urgent need in developing countries, where its prevalence is on the rise. Available data shows that Tharaka Nithi County is one of the regions with high hypertension burden in the Kenya. Information on the adoption and implementation of HTN management guidelines is either limited or completely lacking. We evaluated the level of utilization of HTN management guidelines among primary healthcare facilities in Tharaka Nithi County. The study adopted a cross – sectional analytical design. Ninety-three healthcare facilities were sampled using a multi-stage sampling technique and data collected using the modified World Health Organization (WHO) Service Availability and Readiness Assessment (SARA) questionnaire. The data were analyzed using the Statistical Package of Social Sciences (SPSS) version 27 for both descriptive statistics and inferential statistics. Ethical approval was obtained from the Kabarak University Research Ethics Committee (KUREC) and data collection permit from the National Commission of Science, Technology and Innovation (NACOSTI). Most of the health facilities (96.8%) diagnose and manage HTN patients. Only a third (32.3%) of the facilities received a support supervision visit more than two years ago. A third (34.4%) of the health facilities had a guideline utilization score of two and a mean score of 2.11. The majority (64.5%, n=60) of health facilities reported unsatisfactory utilization of guidelines in the management of hypertension. Healthcare facility category was found to have a significant association with the availability of national guidelines (P = 0.001). ANOVA test showed a statistically significant difference in the mean guideline score based on the type of health facility. Health centres had the highest score while private medical clinics had the lowest score (F = 5.270, P value = 0.007). Statistically significant differences were noted in guideline utilization among dispensaries and health centres. The study reveals a notable deficiency in hypertension management guideline utilization (64.5% reporting suboptimal adherence), compounded by infrequent support supervision visits (32.3% without visits in over two years). The significant association between healthcare facility category and national guideline availability, along with variations in mean scores, highlights the need for targeted interventions to address existing disparities. We recommend implementation of a systematic support framework, ensuring regular support supervision visits for all health facilities, prioritizing those lacking oversight for an extended period. Tailored interventions, particularly for private medical clinics with lower guideline scores, are essential.
Keywords: Blood pressure; Guidelines utilization; Hypertension; Non-communicable diseases; Primary healthcare facilities